Preparation method of gyromagnetic ferrite material applied to high-power microwave device
Through specific proportions of oxide ball milling and stepwise heating and calcining, a uniformly distributed presintered composition is formed, and the polyvinyl alcohol solution is granulated and sintered, and finally annealed at a specific oxygen flow rate, solving the problem of uneven distribution of the components of the rotary magnet ferrite material and significantly improving its electromagnetic properties.
Patent Information
- Application Number
- CN202411707442.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The rotary magnet ferrite materials prepared in the prior art have poor diffusion during powder mixing and sintering, resulting in uneven distribution of internal components of the material and affecting its electromagnetic properties.
A specific ratio of Fe2O3, Y2O3, Bi2O3, CaO, ZrO2 is used for ball milling and drying, and a uniformly distributed presintered composition is formed by stepwise heating and calcining and pulverizing ball milling. Then, polyvinyl alcohol solution is added for granulation and sintering, and finally annealing is performed under a specific oxygen flow rate.
The uniformity of the internal component distribution of rotary magnet ferrite materials is achieved, and its electromagnetic performance is improved, especially in high-power microwave devices applications.
Smart Images

Figure BDA0005154845860000101 
Figure BDA0005154845860000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic ceramic materials, and in particular to a method for preparing a gyromagnetic ferrite material used in high-power microwave devices. Background Art
[0002] Ferrite is a non-metallic magnetic material, usually a composite oxide composed of iron and other metal elements. The resistivity of ferrite can reach 102-1011Ω·cm. In terms of dielectric properties, its dielectric constant is generally 8-16, and the dielectric loss tangent can generally reach 10 -3 -10 -4 , the saturation magnetization intensity is generally between 200-5500 Gauss, and the Curie temperature is generally between 100-600℃. According to the crystal structure, ferrites can be divided into three types: spinel type, garnet type and magnetoplumbite type. According to the characteristics and uses of ferrites, they can be divided into five categories: soft ferrites, hard ferrites, gyromagnetic ferrites, moment ferrites, and piezo ferrites. Gyromagnetic ferrite materials are different from other soft magnetic and hard magnetic ferrite materials. Other magnetic materials generally work by using their "magnetic" characteristics; while gyromagnetic ferrite materials themselves do not show magnetism. Under the action of an external magnetic field, gyromagnetic materials show tensor permeability, ferromagnetic resonance, Faraday rotation and field shift effect to microwave signals. Using these characteristics, various microwave magnetic devices with excellent performance can be made, such as isolators, circulators, electrically controlled phase shifters, electrically controlled switches, polarizers, electrically tunable filters, oscillators, delay lines, etc. Garnet-type gyromagnetic ferrite material is one of the indispensable magnetic materials that is widely used in military and civilian electronic equipment at home and abroad at present and for a long time to come. It has excellent properties such as low loss, high resistivity, narrow resonance linewidth, etc. in the microwave frequency band, and has extremely high application value.
[0003] Circulators and isolators in microwave devices generally work in the range of -55℃-85℃, which requires that the gyromagnetic ferrite materials used in circulators and isolators can maintain good performance in a wide temperature range. In practical applications, there are many garnet-type gyromagnetic ferrite materials, whose saturation magnetization changes greatly with temperature changes, especially in high-power microwave devices. Not only does the change in ambient temperature affect the saturation magnetization of the ferrite, but the ferrite material itself generates a lot of heat due to the high working power of the device, and because the ferrite substrate is located near the center of the microwave device, its heat dissipation rate is not as fast as the heat dissipation of the external magnetic field. Therefore, the temperature of the ferrite itself is higher than the temperature of the external magnetic field. The change amplitude of the saturation magnetization of the ferrite material is always greater than the change amplitude of the external magnetic field. At this time, the saturation magnetization of the ferrite substrate in the circulator and isolator will change greatly, thereby deteriorating the performance indicators of the circulator and isolator.
[0004] In order to solve this problem, patent technology document CN115331907B discloses a preparation method of a gyromagnetic ferrite material for high-power microwave devices, which uses Fe2O3, Y2O3, Gd2O3, Dy2O3, V2O5, ZrO2, Al(OH)3, CaCO3, and MnCO3 as raw materials, calculates the mass ratio of each raw material according to the chemical formula, and weighs the materials; puts the weighed raw materials into a stainless steel ball mill, adds appropriate amounts of steel balls and anhydrous ethanol, seals the ball mill, and ball mills; after the mixed raw materials are ball milled once, the anhydrous ethanol is dried, the mixed raw materials are pressed into round cakes, and are pre-fired in a high-temperature electric furnace; the pre-fired mixture is broken up, put into a stainless steel ball mill, adds appropriate amounts of steel balls and anhydrous ethanol, seals, and ball mills; the mixed powder after the second ball milling is dried, and polyvinyl alcohol solution is added for granulation; pressed into green billets; and the green billets are placed in a high-temperature electric furnace for oxygen sintering.
[0005] However, these existing preparation methods still have the problem that the prepared gyromagnetic ferrite materials have poor diffusion properties during powder mixing and sintering, resulting in uneven distribution of components inside the material, which affects the electromagnetic properties of the material.
[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop a method for preparing a gyromagnetic ferrite material for use in high-power microwave devices. Summary of the invention
[0007] In view of this, the purpose of the present invention is to propose a method for preparing a gyromagnetic ferrite material for use in high-power microwave devices, so as to solve the problem that the gyromagnetic ferrite material prepared by the prior art has poor diffusion during powder mixing and sintering, resulting in uneven distribution of internal components of the gyromagnetic ferrite material and poor electromagnetic properties.
[0008] Based on the above purpose, the present invention provides a method for preparing a gyromagnetic ferrite material used in high-power microwave devices.
[0009] A method for preparing a gyromagnetic ferrite material used in high-power microwave devices, the preparation method is as follows:
[0010] Step S1. Mix dried Fe2O3, Y2O3, Bi2O3, CaO, and ZrO2, add anhydrous ethanol, ball-mill at 800-1000 rpm for 8-10 h, dry at 120-130 ° C, and sieve to obtain a raw material composition;
[0011] Step S2. The raw material composition and citric acid are mixed and loaded into an alumina sealed can, which is sealed and calcined step by step, then crushed and ball-milled at 300-500 rpm for 24-25 hours, and then dried at 120-130 ° C and sieved again to obtain a pre-sintered composition;
[0012] Step S3. Adding polyvinyl alcohol solution to the pre-sintered composition, stirring at 800-1000 rpm for 1-3 hours, granulating, and then compressing into a green body;
[0013] Step S4. After sintering, the green body is re-sintered, and then annealed for 2-2.5 hours at an oxygen flow rate of 200-210 mL / min to obtain a gyromagnetic ferrite material for high-power microwave devices.
[0014] Preferably, the mass ratio of Fe2O3, Y2O3, Bi2O3, CaO, ZrO2 and anhydrous ethanol in step S1 is 79-79.85: 66-67.74: 9.32-11.65: 0.56-0.95: 1.23-3.7: 35-40.
[0015] Preferably, the aperture size of the sieve during the screening in step S1 is 30-38 μm.
[0016] Preferably, the mass ratio of the raw material composition to citric acid in step S2 is 155-160:10-15.
[0017] Preferably, the stepwise heating calcination process in step S2 is as follows:
[0018] The sealed alumina sealed can is first calcined at 400-600°C for 1-2h, then calcined at 600-800°C for 1-2h, and then calcined at 800-850°C for 6-8h.
[0019] Preferably, the aperture size of the sieve during the second screening in step S2 is 0.15-0.3 mm.
[0020] Preferably, in step S3, the mass ratio of the pre-sintered composition to the polyvinyl alcohol solution is 150-155:15-18.
[0021] Preferably, the concentration of the polyvinyl alcohol solution in step S3 is 5wt%-5.2wt%.
[0022] Preferably, the sintering temperature in step S4 is 870-890° C., the gas pressure is 8-8.5 MPa, and the sintering time is 5-6 h.
[0023] Preferably, the temperature during the re-sintering in step S4 is 890-940° C., the gas pressure is 7-16 MPa, and the sintering time is 1-2 h.
[0024] Beneficial effects of the present invention:
[0025] The invention provides a preparation method of a gyromagnetic ferrite material used in high-power microwave devices. The preparation method comprises the following steps: firstly, dry Fe2O3, Y2O3, Bi2O3, CaO and ZrO2 are mixed in a specific proportion, anhydrous ethanol is added thereto, the mixture is ball-milled and then dried, and a raw material composition is obtained after sieving with a sieve with a specific aperture size; then, the raw material composition and citric acid are mixed in a specific proportion and loaded into an alumina sealed can, the mixture is sealed and calcined at a stepwise temperature increase, the mixture is crushed and ball-milled and then dried, and a pre-sintered composition is obtained after sieving with a sieve with a specific aperture size; a polyvinyl alcohol solution is added to the pre-sintered composition, the mixture is stirred evenly, granulated and compressed into a green compact; finally, the green compact is re-sintered after sintering, and annealed at a specific oxygen flow rate to obtain a gyromagnetic ferrite material with uniform internal component distribution, better electromagnetic performance and broad application prospects. DETAILED DESCRIPTION
[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0027] The sources and properties of some of the raw materials used in the present invention are as follows:
[0028] Fe2O3 was purchased from Zhejiang Yamei Nano Technology Co., Ltd., CAS: 1309-37-1; Y2O3 was purchased from Yumu (Ningbo) New Materials Co., Ltd., CAS: 1314-37-0; Bi2O3 was purchased from Yumu (Ningbo) New Materials Co., Ltd., CAS: 1304-76-3; CaO was purchased from Hubei Weideli Chemical Technology Co., Ltd., CAS: 1305-78-8; ZrO2 was purchased from Yumu (Ningbo) New Materials Co., Ltd., CAS: 1314-23-4; citric acid was purchased from Jiangsu Weizhirun Biotechnology Co., Ltd., CAS: 77-92-7.
[0029] Example 1: A method for preparing a gyromagnetic ferrite material for high-power microwave devices is as follows:
[0030] S1. 79 g of dried Fe2O3, 66 g of Y2O3, 9.32 g of Bi2O3, 0.56 g of CaO, 1.23 g of ZrO2 were mixed and 35 g of anhydrous ethanol was added, ball-milled at 800 rpm for 8 h, and then dried at 120 ° C, and sieved with a sieve with a pore size of 30 μm to obtain a raw material composition;
[0031] S2. 155 g of the raw material composition and 10 g of citric acid were mixed and loaded into an alumina sealed can, sealed and calcined at 400 ° C for 1 h, then calcined at 600 ° C for 1 h, and then calcined at 800 ° C for 6 h, then crushed and ball-milled at 300 rpm for 24 h, and then dried at 120 ° C and sieved again with a sieve with an aperture size of 0.15 mm to obtain a pre-sintered composition;
[0032] Step S3. Add 15 g of a 5 wt% polyvinyl alcohol solution to 150 g of the pre-sintered composition, stir at 800 rpm for 1 h, granulate, and compress into a green compact;
[0033] Step S4. Sintering the green body at 870°C and 8MPa for 5h, then re-sintering at 890°C and 7MPa for 1h, and then annealing at an oxygen flow rate of 200mL / min for 2h to obtain a gyromagnetic ferrite material for high-power microwave devices;
[0034] Example 2: A method for preparing a gyromagnetic ferrite material for high-power microwave devices is as follows:
[0035] S1. 79.3 g of dried Fe2O3, 66.54 g of Y2O3, 10 g of Bi2O3, 0.67 g of CaO, and 1.9 g of ZrO2 were mixed and 37 g of anhydrous ethanol was added, ball-milled at 880 rpm for 8.5 h, and then dried at 125 ° C. The raw material composition was obtained by sieving with a sieve having a pore size of 35 μm;
[0036] S2. 157 g of the raw material composition and 12 g of citric acid were mixed and loaded into an alumina sealed can, sealed and calcined at 480 ° C for 1.2 h, then calcined at 680 ° C for 1.4 h, and then calcined at 820 ° C for 6.5 h, then crushed and ball-milled at 370 rpm for 24.5 h, and then dried at 123 ° C and sieved again with a sieve with an aperture size of 0.18 mm to obtain a pre-sintered composition;
[0037] S3. In 152g of the pre-sintered composition, 16g of a 5.1wt% polyvinyl alcohol solution was added, stirred at 880rpm for 1.7h and granulated, and then compressed into a green body;
[0038] S4. The green body was sintered at 877°C and 8.2 MPa for 5.3 h, then re-sintered at 900°C and 10 MPa for 1.3 h, and then annealed at an oxygen flow rate of 203 mL / min for 2.2 h to obtain a gyromagnetic ferrite material for high-power microwave devices;
[0039] Example 3: A method for preparing a gyromagnetic ferrite material for high-power microwave devices is as follows:
[0040] S1. 79.65 g of dried Fe2O3, 67.24 g of Y2O3, 11 g of Bi2O3, 0.8 g of CaO, and 2.5 g of ZrO2 were mixed and then 38 g of anhydrous ethanol was added, ball-milled at 920 rpm for 9.5 h, and then dried at 127 ° C. The raw material composition was obtained by sieving with a sieve having a pore size of 36 μm;
[0041] S2. 158 g of the raw material composition and 14 g of citric acid were mixed and loaded into an alumina sealed can, sealed and calcined at 530 ° C for 1.8 h, then calcined at 730 ° C for 1.7 h, and then calcined at 840 ° C for 7.5 h, then crushed and ball-milled at 430 rpm for 24.7 h, and then dried at 127 ° C and sieved again with a sieve with an aperture size of 0.21 mm to obtain a pre-sintered composition;
[0042] S3. 17 g of a 5.1 wt% polyvinyl alcohol solution was added to 154 g of the pre-sintered composition, stirred at 950 rpm for 1.7 h, and then granulated and compressed into a green body;
[0043] S4. The green body was sintered at 885°C and 8.4MPa for 5.6h, then re-sintered at 920°C and 15.5MPa for 1.7h, and then annealed at an oxygen flow rate of 205mL / min for 2.3h to obtain a gyromagnetic ferrite material for high-power microwave devices;
[0044] Example 4: A method for preparing a gyromagnetic ferrite material for use in high-power microwave devices is as follows:
[0045] S1. 79.85 g of dried Fe2O3, 67.74 g of Y2O3, 11.65 g of Bi2O3, 0.95 g of CaO, and 3.7 g of ZrO2 were mixed and added with 40 g of anhydrous ethanol, ball-milled at 1000 rpm for 10 h, and then dried at 130 ° C. The raw material composition was obtained by sieving with a sieve having a pore size of 30-38 μm;
[0046] S2. 160 g of the raw material composition and 15 g of citric acid were mixed and loaded into an alumina sealed can, sealed and calcined at 600 ° C for 2 h, then calcined at 800 ° C for 2 h, and then calcined at 850 ° C for 8 h, then crushed and ball-milled at 500 rpm for 25 h, and then dried at 130 ° C and sieved again with a sieve with an aperture size of 0.3 mm to obtain a pre-sintered composition;
[0047] S3. In 155g of the pre-sintered composition, 18g of a 5.2wt% polyvinyl alcohol solution was added, stirred at 1000rpm for 3h and granulated, and then compressed into a green body;
[0048] S4. The green body was sintered at 890°C and 8.5 MPa for 6 h, then re-sintered at 940°C and 16 MPa for 2 h, and then annealed at an oxygen flow rate of 210 mL / min for 2.5 h to obtain a gyromagnetic ferrite material for high-power microwave devices;
[0049] Comparative Example 1:
[0050] Compared with Example 1, this comparative example only replaces the "79g of Fe2O3, 66g of Y2O3, 9.32g of Bi2O3, 0.56g of CaO, and 1.23g of ZrO2" added in the preparation process of the raw material composition with "79g of Fe2O3, 66g of Y2O3, 3.32g of Bi2O3, 3.56g of CaO, and 4.23g of ZrO2", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a gyromagnetic ferrite material for high-power microwave devices is obtained;
[0051] Comparative Example 2:
[0052] Compared with Example 1, this comparative example only replaces the "sieve with a pore size of 30 μm" used in the preparation process of the raw material composition with a "sieve with a pore size of 0.85 mm", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains a gyromagnetic ferrite material for high-power microwave devices;
[0053] Comparative Example 3
[0054] Compared with Example 1, this comparative example does not add citric acid during the preparation of the pre-sintered composition, and the remaining steps and parameters are the same, which will not be repeated in this comparative example. Finally, a gyromagnetic ferrite material for high-power microwave devices is obtained;
[0055] Comparative Example 4:
[0056] Compared with Example 1, this comparative example only replaces the process of preparing the pre-sintered composition with "calcining at 400°C for 1h, then calcining at 600°C for 1h, and then calcining at 800°C for 6h after sealing" by "calcining at 800°C for 8h after sealing", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a gyromagnetic ferrite material for high-power microwave devices is obtained;
[0057] Comparative Example 5:
[0058] Compared with Example 1, this comparative example only replaces the "sieve with a pore size of 0.15 mm" used in the preparation process of the pre-sintered composition with a "sieve with a pore size of 0.85 mm", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains a gyromagnetic ferrite material for high-power microwave devices;
[0059] Comparative Example 6:
[0060] Compared with Example 1, this comparative example only replaces the step "annealing for 2h at an oxygen flow rate of 200mL / min" used in the preparation process of the gyromagnetic ferrite material for high-power microwave devices with "annealing for 2h at an air flow rate of 200mL / min", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the gyromagnetic ferrite material for high-power microwave devices is obtained;
[0061] Comparative Example 7:
[0062] Compared with Example 1, this comparative example only replaces the step of "sintering the green body at 870°C and 8MPa for 5h, and then re-sintering at 890°C and 7MPa for 1h" used in the preparation process of the gyromagnetic ferrite material for high-power microwave devices with "re-sintering the green body at 890°C and 7MPa for 6h", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally the gyromagnetic ferrite material for high-power microwave devices is obtained;
[0063] Comparative Example 8:
[0064] Compared with Example 1, this comparative example only replaces the method used in the preparation process of the gyromagnetic ferrite material for high-power microwave devices of "sintering the green body at 870°C and 8MPa for 5 hours, and then re-sintering at 890°C and 7MPa for 1 hour" with "sintering the green body at 870°C and 0MPa for 5 hours, and then re-sintering at 890°C and 0MPa for 1 hour". The remaining steps and parameters are the same and will not be repeated in this comparative example. Finally, the gyromagnetic ferrite material for high-power microwave devices is obtained.
[0065] Performance Testing:
[0066] Determination of saturation magnetization:
[0067] The saturation magnetization of the gyromagnetic ferrite material samples prepared in Examples 1 to 4 and Comparative Examples 1 to 8 was measured using a vibrating sample magnetometer (Changchun Yingpu Magnetoelectric Technology Development Co., Ltd., VSM-220);
[0068] Determination of ferromagnetic resonance line width:
[0069] The gyromagnetic ferrite material samples prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were processed into spheres with a diameter of 0.6 mm, and then placed in a TE106 transmission resonant cavity, with the center frequency set to 9.3 GHz, and then the ferromagnetic resonance line widths of the gyromagnetic ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were measured;
[0070] Determination of dielectric constant:
[0071] The dielectric constants of the gyromagnetic ferrite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were measured using an impedance analyzer (Ernst Instruments, Inc., E4991B) at a frequency of 1 MHz.
[0072] Table 1
[0073]
[0074]
[0075] Data Analysis:
[0076] As can be seen from Table 1, the saturation magnetization intensity, ferromagnetic resonance line width and dielectric constant of the gyromagnetic ferrite material prepared by the present invention are shown in Table 1. These data all indicate that the gyromagnetic ferrite material prepared by the present invention has better electromagnetic properties.
[0077] This may be due to the fact that the specific proportion of Fe2O3, Y2O3, Bi2O3, CaO, and ZrO2 added in the present invention is ball-milled and then dried, and then sieved with a sieve with a specific aperture size to obtain a raw material composition, which can provide the best calcination raw material for the preparation of the pre-sintered composition; then, these processed raw material compositions and citric acid are mixed in a specific proportion to form a complex, thereby reducing the agglomeration of metal ions and making the metal ions evenly dispersed in the solution, which helps in the subsequent sintering process. The various components in the material can be more evenly distributed, thereby improving the quality and performance of the ceramic. At the same time, citric acid will decompose and burn during the sintering process, and the generated gas can form pore channels inside the ceramic material, promote the transmission and diffusion of substances, thereby reducing the temperature required for sintering, which can not only save energy and reduce production costs, but also reduce the influence of high temperature on the structure and performance of ceramic materials; the present invention adopts step-by-step temperature calcination to further promote the uniform distribution of components in the material; then the present invention performs crushing, ball milling, and drying, After sieving again with a sieve with a specific aperture size, a pre-sintered composition is obtained, which can make the components in the prepared green body dispersed more evenly; in the present invention, the green body is finally sintered at a lower temperature first and then re-sintered at a higher temperature, and a specific gas pressure is applied during the entire sintering process, and annealing is performed at a specific oxygen flow rate. This is because compared with direct high-temperature sintering, first sintering at a suitable lower temperature and then re-sintering at a higher temperature can make the distribution of the components in the material more uniform, and the porosity of the sintered gyromagnetic ferrite material will be greatly reduced; compared with pressureless sintering, the pore width of the sample under hot pressing sintering is significantly reduced, so the obtained ferromagnetic resonance line width will also be lower, and the overall electromagnetic properties of the prepared gyromagnetic ferrite material will also be significantly improved, with a lower ferromagnetic resonance line width, which means lower magnetic loss; compared with air annealing, the electromagnetic properties of the gyromagnetic ferrite material prepared by annealing at a specific oxygen flow rate will also be improved; therefore, the internal components of the gyromagnetic ferrite material prepared by the present invention are evenly distributed and have better electromagnetic properties.
[0078] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0079] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a gyromagnetic ferrite material for high-power microwave devices, characterized in that: The preparation method is as follows: Step S1. Mix dried Fe2O3, Y2O3, Bi2O3, CaO, and ZrO2, add anhydrous ethanol, ball-mill at 800-1000 rpm for 8-10 h, dry at 120-130 ° C, and sieve to obtain a raw material composition; Step S2. The raw material composition and citric acid are mixed and loaded into an alumina sealed can, which is sealed and calcined step by step, then crushed and ball-milled at 300-500 rpm for 24-25 hours, and then dried at 120-130 ° C and sieved again to obtain a pre-sintered composition; Step S3. Adding polyvinyl alcohol solution to the pre-sintered composition, stirring at 800-1000 rpm for 1-3 hours, granulating, and then compressing into a green body; Step S4. After sintering, the green body is re-sintered, and then annealed for 2-2.5 hours at an oxygen flow rate of 200-210 mL / min to obtain a gyromagnetic ferrite material for high-power microwave devices.
2. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The mass ratio of Fe2O3, Y2O3, Bi2O3, CaO, ZrO2 and anhydrous ethanol in step S1 is 79-79.85: 66-67.74: 9.32-11.65: 0.56-0.95: 1.23-3.7: 35-40.
3. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The pore size of the sieve during the screening in step S1 is 30-38 μm.
4. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The mass ratio of the raw material composition to citric acid in step S2 is 155-160:10-15.
5. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The step-by-step heating and calcining process in step S2 is as follows: The sealed alumina sealed can is first calcined at 400-600°C for 1-2h, then calcined at 600-800°C for 1-2h, and then calcined at 800-850°C for 6-8h.
6. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The aperture size of the screen during the second screening in step S2 is 0.15-0.3 mm.
7. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The mass ratio of the pre-sintered composition to the polyvinyl alcohol solution in step S3 is 150-155:15-18.
8. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The concentration of the polyvinyl alcohol solution in step S3 is 5wt%-5.2wt%.
9. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The sintering temperature in step S4 is 870-890° C., the gas pressure is 8-8.5 MPa, and the sintering time is 5-6 h.
10. The method for preparing a gyromagnetic ferrite material for high-power microwave devices according to claim 1, characterized in that: The temperature during the re-sintering in step S4 is 890-940° C., the gas pressure is 7-16 MPa, and the sintering time is 1-2 h.
Citation Information
Patent Citations
A gyromagnetic ferrite material for high-power microwave devices and its preparation method
CN115331907B
Narrow-linewidth and low-loss gyromagnetic ferrite material and preparation method thereof
CN104496450A
High-dielectric-constant microwave ferrite material, preparation method and microwave communication device
CN111285673A
Ferrite material and preparation method and application thereof
CN112358290A
Ferrite material, preparation method and microwave communication device
CN115340371A